PENGARUH PENERAPAN I.S.O 9001:2000, KUALITAS PRODUK DAN LAYANAN TERHADAP KEPUTUSAN PEMBELIAN - Melyana ,; Zahrida Z Wiryawan (Universitas Trisakti, 2012)
This research attempted to investigate which variables had been the determinants: ISO 9001:2000, quality of product and quality of service; as influencers of the customers purchasing decisions of the roof products.Using a quantitative design with 113 respondents, the 'f test and 't' test indicated that the implementation of the ISO 9001:2000, quality of the products as well the quality of its services did simultaneously and partially influence customers purchasing decision of the company's roof products positively.Keywords: ISO 9001:2999, Product quality, Customer service quality, Customer purchase decision